Hubungan Data Surveilans dengan Data Google Trends Penyakit Demam Berdarah Dengue di Sulawesi Tenggara, Indonesia - Tosepu, Ramadhan; Susilawaty, Andi; Asis, Muh. Abdul (HIGIENE: Jurnal Kesehatan Lingkungan, 2024)
Dengue Hemorrhagic Fever (DHF) is a disease caused by dengue virus infection through the Aedes mosquitoes bites, especially Aedes aegypti. This study aims to analyze surveillance data with google trends data on dengue hemorrhagic fever in Southeast Sulawesi. This research is a quantitative research with a descriptive approach using time series data. Google search trend in the form of ’DHF Symptoms’ has a correlation with DHF cases with r= 0.697. Time series Google Trends data shows a linear pattern related to surveillance data. Time series Google Trends data shows a linear pattern related to surveillance data where the highest correlation occurs in the entire period of DHF cases with Google Trends ’DHF symptoms’, namely 0.697*. Keywords : Google trends, dengue hemorrhagic fever, surveillance.